Gingivectomy and flap operation procedure with papilla preservation technique in pyogenic granuloma patient - Sandra O. Kuswandani (DiscoverSys Inc., 2018)
Objective: Pyogenic granuloma is one of commonest gingival enlargement in oral cavity or skin, tumor-like, and non-neoplastic lesion. Eventhough, the exact etiology is unknown, but estimated result from chronic irritation or trauma.Methods: This case reported a male patient, 28 years old with 15 milimetres in diameter gingival enlargement in middle anterior of upper jaw region, reddish, bleeding but without any pus. He is using toothpicks and suddenly impaled to the gingiva one week ago. The gingiva slowly enlarged in one week. Gingivectomy and flap operation procedure with papilla preservation technique were done with the intention of removing the lesion. Then, it sent to Pathology laboratorium to enforce the diagnosis.Results: The histopathology result the lesion as pyogenic granuloma. After two weeks follow up, no reccurency for the lesion. And the challenge to avoid gingival recession in anterior region is minimized with papilla preservation technique.Conclusion: Pyogenic granuloma occur the most frequently in the anterior gingiva. The patient sometimes did not realize the main cause and the process of the enlargement until interfere the quality of life. Dentist should know the disease, the etiology and pathogenesis, and should understand when to refer to specialist.